ANTIOXIDANT ACTIVITY AND CYTOTOXICITY TEST OF EXTRACT COMBINATION OF JAMBU BOL LEAF (Syzygium malaccense L.), MANILA SAPODILLA LEAF (Manilkara zapota L.) AGAINST HSC-3 CELL LINE - Mazer, Aryadita Ramadhani; Marsiati, Himmi (HEARTY, 2025)
In the herbal plants of jambu bol (Syzygium malaccense L.) and manila sapodilla (Manilkara zapota L.), especially in the leaves of the plant, it contains very strong antioxidants. According to research by Zaen Devi Maulani and Ekayanti Meiliza, the antioxidant activity value of ethanol extract of jambu bol leaves (Syzygium malaccense L.) is 3.297 ± 2.595 ppm and for ethanol extract of manila sapodilla leaves (Manilkara zapota L.) is 8.2786 μg/mL. The antioxidant activity of a compound is said to have very strong antioxidants if the IC₅₀ value is less than 50 ppm, strong IC₅₀ if the IC₅₀ value ranges from 50-100 ppm, moderate if the IC₅₀ value ranges from 100-150 ppm, and weak if the IC₅₀ value ranges from 150-200 ppm. This study is an experimental laboratory by measuring the antioxidant activity value (IC₅₀) using different solvents in the combination of the two simplicia and the toxicity concentration of the combination of the two simplicia using the CCK-8 assay method. The samples used were tested for determination to determine and ensure that the materials used were the correct samples to be tested and made into extracts. Furthermore, the extraction of samples with solvents was concentrated with a rotary evaporator to separate the active substances and solvents. The results of this study indicate that there is no significant difference in the antioxidant activity of the combination of jambu bol leaf extract (Syzygium malaccense L.) and manila sapodilla leaf extract (Manilkara zapota L.) in the positive control (ascorbic acid). There is a significant difference in the cytotoxicity of jambu bol leaf extract (Syzygium malaccense L.) and manila sapodilla leaf extract (Manilkara zapota L.) in the positive control (DMSO) on the viability of HSC-3 cells. The combination of jambu bol leaf extract (Syzygium malaccense L.) and sapodilla leaf extract (Manilkara zapota L.) at a concentration of 5-160 µg/mL did not show any cytotoxic effect on the viability of HSC-3 cells.